Altering maize (Zea mays) seedlings’ growth and lignification processes by action of novel synthesized compounds - Y. V. Lykholat; N. O. Khromykh; O. O. Didur; O. O. Gaponov; M. M. Nazarenko; T. Y. Lykholat (Regulatory Mechanisms in Biosystems, 2021)
Effective management of the course of crop vegetation and adaptation to biotic and abiotic stresses is a prerequisite for stable grain production and requires replenishment of the arsenal of plant growth regulators. The effect of novel synthesized cage amides on maize seedlings morphogenesis has been tested. Seeds of a mid-early maize hybrid 'DN Galatea' after the pre-sowing treatment with 0.01% solutions of test compounds were grown in distilled water. The roots and shoots sections of 10-day-old maize seedlings were stained with phloroglucinol solution to reveal the lignin-containing anatomical structures. The effects of nine different test compounds, exceeding the well-known effects of the phytohormone auxin, promoted the maize seedlings’ linear growth, increased wet weight of roots and shoots, and dry biomass accumulation both in seedlings roots and shoots. Several test compounds activated the dry weight accumulation process without significantly affecting the root and shoot length. In the maize seedlings’ roots, an increase in the diameter and number of the xylem vessels was found, as well as an increase in the lignin-containing layer thickness of the endoderm cells in the root cortex. In the maize seedlings’ shoots, the test compounds caused an increase in the thickness of the lignin-containing outer layer of the seedlings’ first leaf. In general, the test compounds’ effect on seedling roots can potentially enhance root formation; increase efficiency of the roots water-conducting system and the tissues’ strength, thus reducing the likelihood of root lodging in maize plants. The effects of the test compounds revealed in the seedlings’ shoots reflect the activation of the shoots’ structure formation and may have a positive value for enhancing the strength of the plant stems and counteracting the stem lodging of the maize plants.